Is the comprehension of idiomatic sentences indeed impaired in paranoid Schizophrenia? A window into semantic processing deficits - Pesciarelli, Francesca; Gamberoni, Tania; Ferlazzo, Fabio; Lo Russo, Leo; Pedrazzi, Francesca; Melati, Ermanno; Cacciari, Cristina (Frontiers in Human Neuroscience, 2014)
Schizophrenia patients have been reported to be more impaired in comprehending non-literal than literal language since early studies on proverbs. Preference for literal rather than figurative interpretations continues to be documented. The main aim of this study was to establish whether patients are indeed able to use combinatorial semantic processing to comprehend literal sentences and both combinatorial analysis and retrieval of pre-stored meanings to comprehend idiomatic sentences. The study employed a sentence continuation task in which subjects were asked to decide whether a target word was a sensible continuation of a previous sentence fragment to investigate idiomatic and literal sentence comprehension in patients with paranoid schizophrenia. Patients and healthy controls were faster in accepting sensible continuations than in rejecting non-sensible ones in both literal and idiomatic sentences. Patients were as accurate as controls in comprehending literal and idiomatic sentences, but they were overall slower than controls in all conditions. Once the contribution of cognitive covariates was partialled out, the response times to sensible idiomatic continuations of patients did not significantly differ from those of controls. This suggests that the state of residual schizophrenia did not contribute to slower processing of sensible idioms above and beyond the cognitive deficits that are typically associated with schizophrenia.